2016
DOI: 10.5812/ircmj.26994
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Unwanted Pregnancies among Multiparous Mothers in Khorramabad, Iran

Abstract: Background: Unwanted pregnancy is the kind of pregnancy which is undesirable for at least one of the parents, and is accompanied by unfavorable consequences for the family and society. Objectives: In this study, three classification models have been used to predict the occurrence of unwanted pregnancies in the urban population in Khorramabad, Iran, and the performance of these models was compared. Methods: In this cross-sectional study, 467 multiparous mothers referred to the health centers of Khorramabad in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…There has been a wide variation in the recently reported prevalence of unintended pregnancy in different cities of Iran[ 8 15 16 17 18 19 20 21 22 23 24 ] [ Table 4 ]. The highest prevalence of unwanted pregnancy was reported in Rasht City at (49.3%)[ 17 ] and the lowest was in Semnan City at (10.5%).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a wide variation in the recently reported prevalence of unintended pregnancy in different cities of Iran[ 8 15 16 17 18 19 20 21 22 23 24 ] [ Table 4 ]. The highest prevalence of unwanted pregnancy was reported in Rasht City at (49.3%)[ 17 ] and the lowest was in Semnan City at (10.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they did not apply the elastic net regression algorithm in their analysis. On the contrary, the neural network produced the highest area under the ROC curve compared to other machine learning algorithms included in their studies [ 39 , 40 ]. To predict unwanted pregnancy among women aged 35 or more in Iran, Nouhjah and Kalhori applied artificial neural networks and revealed that the area under the curve for artificial neural was 0.67 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health indicators serve as a reflection of the overall health of a society, and those related to infants hold particular significance in assessing societal health (2). Neglecting to monitor infant growth indicators can lead to severe complications, including increased mortality (3), diminished cognitive and physical development, and emotional or physical disabilities (4). Therefore, it is crucial to track the growth and development of infants, detect deviations from the normal growth patterns early on, and prevent complications (5).…”
Section: Introductionmentioning
confidence: 99%